P PENINGKATAN KEMAMPUAN KADER DALAM PERTOLONGAN PERTAMA PADA KECELAKAAN DI DAERAH PINGGIRAN SUNGAI DI DESA BURAI KEBUPATEN OGAN ILIR - Yamin, M; Apriani, Dwi; Febriati, Tri; Anggraini, Desy; M Hasan (Jurnal Abdimas Musi Charitas, 2023)
Accidents can happen anywhere, at home, on the go, at work, and anywhere else. As a result of an accident, the victim may experience minor or serious injuries, fainting, disability for life or even death. For victims who died, of course, they do not need a fast form of help, but for accident victims who are still alive, they need fast and appropriate help so that the victim can avoid the danger of death. The community, especially the health center cadres in the Tanjung Batu Health Center Work Area, want to overcome and increase their knowledge and skills in first aid for accidents. Not yet know how to handle first aid in accidents in the local community. So far this knowledge, understanding, insight, and skills have not been realized due to a lack of understanding of human resources in increasing knowledge and skills in first aid in accidents. Therefore, this service aims to provide education and first aid methods for accidents in the area around the village. The service method carried out includes an explanation of first aid in an accident first. After that, the servant demonstrated first aid movements in front of the cadres. The evaluation obtained was the enthusiasm of the cadres in participating in counseling activities and the practice of first aid movements in accidents. The cadres are able to answer correctly every question given by the servant. In addition, the cadres are able to properly demonstrate how to provide first aid in an accident. This activity is expected to provide a touch of knowledge related to first aid in accidents so that they are able to provide assistance to the community.